The Role of the Nagari Government in Empowering Women Farmers Groups (WFG) Producing Processed Cinnamon Products in Nagari Malalak Barat - Aprilia, Natasya; Eriyanti, Fitri (The Future of Education Journal, 2025)
This research is motivated by the significant potential of cinnamon commodities in Nagari Malalak Barat, Agam Regency, managed by the Women's Farmers Group (KWT) to produce various processed products. However, the empowerment efforts carried out by the Nagari Government still face several obstacles, such as the lack of policy support, limited market access, and insufficient continuous training. This study aims to describe the role of the Nagari Government in empowering KWT, as well as to identify the supporting and inhibiting factors. The research uses a qualitative approach with data collection techniques including interviews, observations, and document studies. The results show that the role of the Nagari Government can be seen in its functions as a regulator, dynamizer, and facilitator, but its implementation has not been optimal. Supporting factors include the potential of the commodities and initial government support, while inhibiting factors include limited capital, technology, and regulations. Therefore, more concrete and sustainable strategies are needed to enhance the independence of KWT.